Karakteristik Fenotipik Sifat Kualitatif Kambing Lokal Di Kecamatan Bula Kabupaten Seram Bagian Timur - Rumfot, Riansya; Papilaya, Bercomien J.; Rajab, Rajab (Universitas Pattimura, 2023)
Expression of qualitative traits may represent several adaptive mechanisms related to adaptation and survival in different ecological zones where local goats are located. The purpose of this study was to study the phenotypic characterization of qualitative traits such as coat color and horn characteristics of local goats in Bula District, East Seram District. The research took place from October to November 2022 in Bula District, East Seram Regency, Maluku Province, because this area is an area for developing goat livestock where the population reaches 32.18% of the total ruminant livestock. Direct observation in the field (observatory design) of a total of 100 local goats randomly selected in 3 samples, namely Engglas Village, Bula Air, and Fault. The variables observed were qualitative characteristics related to outward appearances, such as body morphology, horns, back, ears, and color patterns. The results showed that local goats in Bula District had qualitative characteristics including a flat facial profile with normal eyes (100%), dominated by goats with horns (90%) and dangling ears (78%), with a concave dorsal line (100 %). The color pattern of the fur is still very varied, some are black (17%), white (20%), gray (16%), brown (23%) and the remaining 24% have a mixed color of black, white, and brown. Based on these qualitative characteristics, it belongs to the kacang goat breed.